Research skills and creativity levels in 4-year-old preschoolers - Huamán Galindo, Maribel (2023)
The present research paper was developed to determine the relationship between investigative skills and levels of creativity, being of a quantitative type and of a nonexperimental descriptive correlational design. The data was gathered through two self-made observation guides validated by expert judgment, titled “Observation Guide for Investigative Skills” and Observation Guide for Creativity Levels“. Forty 4-year-old children were part of the sample from a preschool located in MetropolitanLima. The application of the instruments was carried out through Zoom sessions,in the context of remote learning due to the current Covid-19 pandemic. The results indicate that there is a close relationship among both studied variables. I’m addition, we recognized the importance of working on research and creativity from the preschool stage.